Synergistic conservation approaches for nurturing soil, food security and human health towards sustainable development goals - Pandian, Kannan; Mustaffa, Mohamed Roshan Abu Firnass; Mahalingam, Govindaraj; Paramasivam, Arunachalam; Prince, Abishek John; Gajendiren, Manimaran; Mohammad, Abdul Rahman Rafiqi; Varanasi, Surya Teja (Elsevier, 2024)
Using chemical fertilizers extensively in small farms has helped increase crop yields, supporting food security and economic growth. However, recent studies show that these fertilizers are often used inefficiently and inconsistently. This leads to environmental harm, unbalanced soil nutrients, and lower-quality food production. These issues threaten food security, which is vital for human survival and may lead to the abandonment of arable land. This situation calls for a significant shift in soil conservation research to better connect scientific findings with practical conservation methods, ensuring that agricultural progress goes hand in hand with environmental sustainability. Effective use of nitrogen (N), phosphorus (P), and potassium (K) fertilizers is vital for both environmental sustainability and food security. Correcting nutritional imbalances, especially the disrupted N/P ratio caused by faulty fertilization practices, is key to ensuring a balanced nutrient supply. These imbalances have a substantial effect on aquatic and terrestrial ecosystems, altering their functionality, biodiversity and human nutrition Therefore, adopting balanced fertilization techniques is essential to combine environmental sustainability with global food security and achieve the Sustainable Development Goals (SDGs).To optimize nutrient consumption and production efficiency, regulations should be enacted to enforce the 4R principle, which involves applying the right nutrient source at the appropriate rate, time, method and location. This article emphasizes the connections between current agricultural practices, land use, fertilizer application, soil degradation, and future challenges. It promotes environmentally friendly farming methods that recognize the vital links between soil quality, food security, human health, and environmental sustainability.